2004
DOI: 10.1074/jbc.m311715200
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-mediated Endocytosis of Na+,K+-ATPase in Response to Parathyroid Hormone Requires ERK-dependent Phosphorylation of Ser-11 within the α1-Subunit

Abstract: Parathyroid hormone (PTH) inhibits Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 25 publications
2
54
2
Order By: Relevance
“…It involves lysosomal breakdown of Na/Pi-II proteins as a result of activation of several protein kinases (PK) (5). These include PKA, PKC, and PKG and the ERK/MAPK pathway (4,21,43,44). The NHERF-1 interacts directly with the Na/Pi-4 transporter and is involved in the signaling pathway of PTH inhibition of P uptake by OK cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…It involves lysosomal breakdown of Na/Pi-II proteins as a result of activation of several protein kinases (PK) (5). These include PKA, PKC, and PKG and the ERK/MAPK pathway (4,21,43,44). The NHERF-1 interacts directly with the Na/Pi-4 transporter and is involved in the signaling pathway of PTH inhibition of P uptake by OK cells (21).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Na,K-ATPase activity could either be stimulated or inhibited by ERK1/2-dependent phosphorylation of the ␣ 1 subunit (4,35). Long term stimulation of ERK1/2 has been shown to inhibit transcription of ENaC subunits in mouse collecting duct cells (mCT1) and in salivary epithelial cells (36 -38).…”
Section: Erk1/2 Controls Nak-atpase Activity In the Principal Cellmentioning
confidence: 99%
“…In the kidney, the ERK1/2 pathway is involved in the hormonal regulation of different apical and basolateral channels or transporters expressed along the nephron for maintaining the extracellular fluid homeostasis. In the proximal tubule the ERK1/2 pathway is involved in the internalization of the Na ϩ /phosphate co-transporter at the apical membrane and in the activation of Na,K-ATPase at the basolateral membrane (3,4). In the thick ascending limb the ERK1/2 pathway is also involved in the inhibition of basolateral Na ϩ /H ϩ exchange activity and HCO 3 Ϫ absorption by nerve growth factor (5).…”
mentioning
confidence: 99%
“…PI3K has been shown to be necessary for the internalization of several growth factor receptors as it controls initial stages of the coated pit assembly (54 -58). Several studies suggest that ERK is not directly involved in the regulation of the clathrin-dependent endocytosis machinery; for the Na,K-ATPase, however, it has been shown that ERK-mediated phosphorylation of the cytoplasmic domain is required for its endocytosis (59).…”
Section: Discussionmentioning
confidence: 99%